Gill Net Selectivity and Stock Assessment of Kugbo Creek in the Delta Region of the River Niger, Nigeria - Edoghotu, Azibodi Jonah (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2024)
Gill net selectivity and stock assessment studies were carried out in Kugbo Creek, in the Delta region of River Niger, Nigeria. Nine-gill nets of varying sizes (¾", 1", 1½", 1¾", 2", 2½", 3½", 4"and 7") were used at 7 hours-day active fishing. Mean biomass of 2,054kg represented the mean total daily catch of 2,243 individuals. Highest mean catch per net was observed in mesh size 2½" with a total mean catch of 653 individuals or 981.31kg biomass that represented 47.78% of the total daily catch. The lowest catch was with 7" mesh, 21 individuals or 130kg biomass per day representing 6.33%. The analytical method of the age composition of catch in the fisheries stock assessment showed there were few old fishes in the fisheries which depicts high fishing pressure (overfishing), which here may have resulted from loss due to pollution. Generally, biomass decreases with decreasing fishing net mesh and increases with increasing mesh sizes.